The rise and fall of tuberculosis in Malawi: associations with HIV infection and antiretroviral therapy. Issue 1 (16th November 2015) - Kanyerere, Henry; Harries, Anthony D.; Tayler‐Smith, Katie; Jahn, Andreas; Zachariah, Rony; Chimbwandira, Frank M.; Mpunga, James
Abstract: Objectives: Since 1985, Malawi has experienced a dual epidemic of HIV and tuberculosis (TB) which has been moderated recently by the advent of antiretroviral therapy (ART). The aim of this study was to describe the association over several decades between HIV/AIDS, the scale‐up of ART and TB case notifications. Methods: Aggregate data were extracted from annual reports of the National TB Control Programme, the Ministry of Health HIV Department and the National Statistics Office. ART coverage was calculated using the total HIV population as denominator (derived from UNAIDS Spectrum software). Results: In 1970, there were no HIV‐infected persons but numbers had increased to a maximum of 1.18 million by 2014. HIV prevalence reached a maximum of 10.8% in 2000, thereafter decreasing to 7.5% by 2014. Numbers alive on ART increased from 2586 in 2003 to 536 527 (coverage 45.3%) by 2014. In 1985, there were 5286 TB cases which reached a maximum of 28 234 in 2003 and then decreased to 17 723 by 2014 (37% decline from 2003). There were increases in all types of new TB between 1998–2003 which then declined by 30% for extrapulmonary TB, by 37% for new smear‐positive PTB and by 50% for smear‐negative PTB. Previously treated TB cases reached a maximum of 3443 in 2003 and then declined by 42% by 2014. Conclusion: The rise and fall of TB in Malawi between 1985 and 2014 was strongly associated with HIV infection and ART scale‐up; this has implications for ending the TB epidemic in high HIV–TB burden countries.